Heterophasic polypropylene composition
By optimizing the nucleating agent combination and comonomer content, the problem of poor impact performance of the heterophase polypropylene composition while increasing the crystallization temperature and stiffness is solved, and high crystallization temperature, good mechanical properties and improved impact performance are achieved.
Patent Information
- Application Number
- CN202180021027.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-03-19
- Filing Date
- 2021-03-17
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2041-03-17
AI Technical Summary
The existing heterophase polypropylene compositions have poor impact performance while increasing the crystallization temperature and stiffness, making it difficult to meet the needs of high stiffness and high impact performance at the same time.
By optimizing the nucleating agent combination and comonomer content of the heterophase polypropylene composition, its responsiveness to the nucleating agent is improved, thereby improving the crystallization temperature and mechanical properties.
The high crystallization temperature, good mechanical properties and improved impact performance of the heterophase polypropylene composition are achieved, and the requirements of having both high stiffness and high impact performance are met.
Smart Images

Figure BDA0003844421090000091 
Figure BDA0003844421090000131 
Figure BDA0003844421090000141
Abstract
Description
Technical Field
[0001] The present invention provides a heterophasic polypropylene composition having good response to nucleating agents, increased crystallization temperature and good mechanical properties. The present invention also relates to articles made therefrom, and the use of the heterophasic polypropylene composition for specific applications and the production of these articles. Background Art
[0002] Heterophasic polypropylene compositions are known in the art. They consist of a continuous propylene homopolymer or copolymer phase as matrix, in which is dispersed an elastomeric phase, such as ethylene-propylene rubber (EPR).
[0003] Heterophasic polypropylene copolymers are widely used in injection molding applications, especially for the production of packaging articles, as they are well known and appreciated for their mechanical properties as well as their very convenient processing. Typical applications are e.g. thin-wall packaging, houseware applications, food containers and other packaging problems.
[0004] The heterophasic polypropylene copolymers are usually further modified with various nucleating agents to increase the crystallization temperature, or to improve mechanical properties like stiffness.
[0005] Higher crystallization temperatures are also required to achieve faster conversions and thus reduce cycle times, for example in injection molding.
[0006] However, this increase in stiffness can have a negative impact on impact properties, making the polymer more brittle.
[0007] Thus, there is usually a conflict of objectives if one wants to provide a heterophasic polypropylene composition having both high stiffness and high impact properties.
[0008] Single site catalysts (SSC) are well known in the field of polypropylene production. Due to their highly random insertion of comonomer units along the chain, they are increasingly used in the copolymerization of propylene with other comonomers.
[0009] It is known that propylene polymers produced with single-site catalysts offer a better stiffness / impact balance than similar polymers produced with Ziegler-Natta catalysts. However, the widely reported SSC-based polymers have a weaker nucleation response due to differences in molecular structure. This is mainly manifested in lower crystallization temperatures than those observed in polymers produced by Ziegler-Natta catalysis while having similar polymer properties, such as comonomer content and type, amount of soluble fraction, etc.
[0010] Description of the prior art:
[0011] M. Varma-Nair et al., in "Quiescent crystallization kinetics of nucleated metallocene and ZN isotactic polypropylenes", (Journal of Thermal Analysis and Calorimetry, 59 (2000) 483-495), report that both α- and β-nucleation reactions in polypropylene copolymers produced by single-site catalysis are inferior to those based on heterogeneous titanium halide (Ziegler-Natta) catalysts, although the respective homopolymers have almost the same crystallization properties. The crystallization temperature of metallocene polypropylene is reported to be up to 123°C, and only limited toughness of the homopolymer is proposed.
[0012] WO / 2020 / 011825 discloses a heterophasic polypropylene composition comprising 60.0 to 95.0 wt% of a crystalline propylene homopolymer, 5.0 to 20.0 wt% of an elastomeric ethylene-propylene rubber and at least one polymer nucleating agent, wherein the crystalline propylene homopolymer (H-PP) and the elastomeric ethylene-propylene rubber (EPR) are produced in the presence of a single-site catalyst. It discloses a polymer having a lower amount of comonomer in the soluble fraction, the polymer having good clarity but very limited toughness, especially at -20°C.
[0013] EP 2075284 A1 discloses heterophasic propylene copolymers with high fluidity, wherein the fraction insoluble in cold xylene (XCI) has an intrinsic viscosity below 1.5 dl / g, the fraction soluble in cold xylene (XCS) has an intrinsic viscosity of 1.5 to 3.0 dl / g and the comonomer content in the fraction soluble in cold xylene (XCS) is 25 to 50 mol%. Examples thereof have an intrinsic viscosity of the fraction insoluble in cold xylene of 0.7 to 0.9 dl / g, an IV of XCI.
[0014] It is designed to have improved impact properties at low temperatures combined with good flow properties, but has poor toughness, especially at -20°C.
[0015] WO / 2019 / 134951 discloses a heterophasic propylene copolymer comprising a) 65 to 90 wt% of a matrix component (M) selected from a propylene homopolymer or a random copolymer (PP); and b) 10 to 35 wt% of an ethylene-propylene rubber (EPR) dispersed in the propylene homopolymer or random copolymer (PP), whereby the xylene cold soluble fraction (XCS) of the heterophasic propylene polymer (HECO) has an ethylene content of 12 to 20 wt%; an intrinsic viscosity (IV) of at least 1.6 dl / g as measured according to ISO 1628-1:2009; and the xylene cold insoluble fraction (XCI) of the heterophasic propylene polymer (HECO) has 2,1 erythro-regional defects in an amount of at least 0.4 mol%. It discusses the addition of nucleating agents.
[0016] The examples disclosed have a comonomer content C2 (XCS) of the soluble fraction between 14.1 and 14.8 wt.-%, good clarity but very limited toughness, especially at -20°C. Summary of the invention
[0017] The present invention overcomes the disadvantages of the prior art. It discloses a heterophasic polypropylene composition having a specific combination of the amount of the soluble fraction in the heterophasic polypropylene composition, its comonomer content and a nucleating agent. This results in a heterophasic polypropylene composition having a good response to the nucleating agent, an increased crystallization temperature and good mechanical properties.
[0018] In particular, it discloses a heterophasic propylene composition comprising
[0019] 99.0 to 99.99 wt.% of a heterophasic propylene copolymer, and
[0020] 0.01 to 1.0 wt.% of a nucleating agent,
[0021] wherein the heterophasic propylene copolymer is characterized by comprising
[0022] i) 65.0 to 90.0 wt. % of a crystalline matrix of a propylene homopolymer or copolymer,
[0023] The crystalline matrix corresponds to a crystalline fraction (CF) determined according to the CRYSTEX QC method, ISO 6427-B, having an intrinsic viscosity IV (CF) in the range of 1.0 to 4.0 dl / g and containing 1.5 to 3.5% by weight of comonomers, and
[0024] ii) 10.0 to 35.0 wt.-% of an amorphous propylene-ethylene elastomer dispersed in said crystalline matrix (i), optionally comprising as further comonomer a C4-C12 alpha-olefin, said amorphous propylene ethylene elastomer (ii) corresponding to the soluble fraction (SF) determined according to the CRYSTEX QC method, ISO 6427-B, and having a comonomer content of the soluble fraction (C2 of SF) in the range of 20.0 to 35.0 wt.-%,
[0025] wherein i) and ii) add up to 100 wt.%,
[0026] It is characterised in that the heterophasic polypropylene composition has a crystallization temperature (Tc) of at least 124 °C.
[0027] The present invention also discloses articles (such as injection molded articles) comprising the heterophasic polypropylene composition and the use of the heterophasic polypropylene composition for producing such articles.
[0028] The polymers of the present invention provide an optimal correlation between the crystallization temperature Tc and the melting temperature Tm. The increase in the crystallization temperature ensures a rapid onset of crystallization, which is more effective during processing than a small degree of undercooling (i.e., a smaller ΔT mc ) is more advantageous. DETAILED DESCRIPTION
[0029] The heterophasic polypropylene composition of the present invention comprises
[0030] a) 99.0 to 99.99 wt.% of a heterophasic propylene copolymer, and
[0031] b) 0.01 to 1.0 wt. % of a nucleating agent.
[0032] Preferably, the heterophasic polypropylene composition comprises 99.2 to 99.95 wt%, preferably 99.5 to 99.9 wt% of the heterophasic propylene copolymer and 0.05 to 0.8 wt%, preferably 0.1 to 0.5 wt% of the nucleating agent.
[0033] Preferably, the heterophasic polypropylene composition of the present invention consists of 99.0 to 99.99 wt% of the heterophasic propylene copolymer and 0.01 to 1.0 wt% of the nucleating agent.
[0034] MFR of the heterophasic polypropylene composition 230 / 2.16 It may be in the range of 0.1 to 100 g / 10 min, preferably in the range of 0.5 to 50 g / 10 min, and more preferably in the range of 1.0 to 20 g / 10 min.
[0035] The crystallization temperature (T c) may be in the range of at least 124 to 135°C, preferably in the range of 125 to 132°C, more preferably in the range of 126 to 130°C.
[0036] The melting temperature (T m ) may be in the range of 150 to 165°C, preferably in the range of 155 to 164°C, more preferably in the range of 157 to 163°C.
[0037] The melting enthalpy of the heterophasic polypropylene composition may be in the range of 70 to 100 J / g, preferably in the range of 75 to 98 J / g, more preferably in the range of 78 to 96 J / g.
[0038] The heterophasic polypropylene composition may have a cold xylene (XCS) soluble fraction in the range of 10.0 to 35.0 wt.-%, preferably in the range of 12.0 to 31.0 wt.-%, more preferably in the range of 14.0 to 28.0 wt.-%.
[0039] Reference is also made to the Crystex method description, where it is noted that the value of XCS corresponds approximately but not exactly to the soluble fraction (SF) determined in Crystex.
[0040] The heterophasic propylene composition is mainly formed of the heterophasic polypropylene copolymer.
[0041] Thus, polymer-related properties like comonomer content or quality, amount and composition of crystalline fraction or soluble fraction, viscosity of crystalline fraction and soluble fraction etc. apply equally to the heterophasic polypropylene composition as well as to the heterophasic propylene copolymer.
[0042] Heterophasic propylene copolymer
[0043] The heterophasic propylene copolymer forms the major part of the heterophasic polypropylene composition, so the former influences the properties of the latter.
[0044] The heterophasic propylene copolymer comprises in the range of 65.0 to 90.0 wt.%, preferably 69.0 to 88.0 wt.%, more preferably in the range of 72.0 to 86.0 wt.% of propylene homo- or copolymer forming a crystalline matrix (i) corresponding to the crystalline fraction CF determined by CRYSTEX QC method ISO 6427-B.
[0045] Thus, the heterophasic polypropylene copolymer comprises in the range of 10.0 to 35.0 wt.-%, preferably in the range of 12.0 to 31.0 wt.-%, more preferably in the range of 14.0 to 28.0 wt.-% of (ii) amorphous propylene ethylene elastomer dispersed in the crystalline matrix. The amorphous elastomer corresponds to the soluble fraction (SF) determined by CRYSTEX QC method ISO 6427-B.
[0046] In a preferred embodiment the heterophasic propylene copolymer consists of:
[0047] i) 65.0 to 90.0 wt%, preferably 69.0 to 88.0 wt%, more preferably in the range of 72.0 to 86.0 wt% of a propylene homopolymer or copolymer forming the crystalline matrix (i), and
[0048] ii) 10.0 to 35.0 wt%, preferably in the range of 12.0 to 31.0 wt%, more preferably in the range of 14.0 to 28.0 wt% of amorphous propylene ethylene elastomer dispersed in said crystalline matrix,
[0049] The heterophasic polypropylene copolymer contains a comonomer, preferably an alpha-olefin, selected from ethylene and C4 to C8 alpha-olefins, preferably selected from ethylene, 1-butene or 1-hexene.
[0050] In a preferred embodiment the heterophasic polypropylene copolymer comprises ethylene and 1-butene as comonomers.
[0051] In an especially preferred embodiment the heterophasic polypropylene copolymer comprises ethylene as the only comonomer.
[0052] The comonomer content C2 (total) of the heterophasic propylene copolymer may be in the range of 1.0 to 10.0 wt.-%, preferably in the range of 2.5 to 8.5 wt.-%, more preferably in the range of 4.0 to 7.5 wt.-%.
[0053] The amount of crystalline fraction (CF) of the heterophasic polypropylene copolymer is determined by CRYSTEX QC method ISO 6427-B and may be in the range of 65.0 to 90.0 wt.-%, preferably in the range of 69.0 to 88.0 wt.-%, more preferably in the range of 72.0 to 86.0 wt.-%.
[0054] The crystalline fraction may comprise comonomers as listed above.The comonomer content C2(CF) of the crystalline fraction may be in the range of 1.5 to 3.5 wt.-%, such as 1.7 to 3.2 wt.-% or 1.7 to 2.8 wt.-%.
[0055] The soluble fraction (SF) of the heterophasic propylene copolymer is also determined by CRYSTEX QC method ISO 6427-B and may be in the range of 10.0 to 35.0 wt.-%, preferably in the range of 12.0 to 31.0 wt.-%, more preferably in the range of 14.0 to 28.0 wt.-%.
[0056] The soluble fraction may contain comonomers as listed above. The comonomer content C2(SF) of the soluble fraction may be in the range of 20.0 to 35.0 wt.-%, preferably in the range of 21.0 to 33.0 wt.-%, more preferably in the range of 21.5 to 31.0 wt.-%, or in the range of 22.5 to 30.0 wt.-%.
[0057] It shall be understood that the quality and amount of comonomers, the crystalline fraction and the solubles fraction in the heterophasic polypropylene copolymer can be selected and varied independently of each other.
[0058] The intrinsic viscosity IV (SF) of the soluble fraction of the heterophasic propylene copolymer may be in the range of 2.0 to 5.0 dl / g, preferably in the range of 2.2 to 4.5 dl / g, more preferably in the range of 2.3 to 4.0 dl / g.
[0059] The intrinsic viscosity IV (CF) of the crystalline fraction of the heterophasic propylene copolymer may be in the range of 1.0 to 4.0 dl / g, preferably in the range of 1.3 to 3.7 dl / g, more preferably in the range of 1.5 to 3.4 dl / g, like in the range of 1.7 to 3.2 dl / g.
[0060] The ratio between IV(SF) and IV(CF) may be in the range of at least 0.83 to 2.5, preferably in the range of 0.85 to 2.2, and more preferably in the range of 0.85 to 2.0.
[0061] The crystalline fraction (CF) of the heterophasic propylene polymer (HECO) may have 2,1 erythro regio defects in an amount of at least 0.3 wt%. Typically the amount of 2,1 erythro regio defects in the xylene cold insoluble fraction (XCI) of the heterophasic propylene polymer (HECO) may not be higher than 2.0 wt%. It may preferably be in the range of 0.5 to 1.5 wt% or 0.6 to 1.2 wt%.
[0062] As is well known in the art, the amount of 2,1-erythro regio defects in propylene homopolymers or random copolymers produced with Ziegler Natta catalysts is 0.0 wt%. Therefore, heterophasic propylene polymers (HECO) are typically produced using single-site catalysts such as metallocene catalysts. Suitable catalysts are provided below.
[0063] Thus, all properties described above for the heterophasic propylene copolymer also apply for the heterophasic polypropylene composition of the present invention.
[0064] The heterophasic propylene copolymer does not contain any nucleating agent. Therefore, the mechanical and / or crystalline properties of the pure polymer will be different from the corresponding properties of the (final) heterophasic polypropylene composition of the present invention:
[0065] The crystallization temperature (T c ) may be in the range of 110 to 125°C, preferably in the range of 111 to 122°C, more preferably in the range of 113 to 120°C.
[0066] The melting temperature (T c ) may be in the range of 150 to 165°C, preferably in the range of 153 to 163°C, more preferably in the range of 155 to 162°C.
[0067] The flexural modulus of the neat heterophasic propylene copolymer may be in the range of 500 to 2000 MPa, preferably in the range of 600 to 1600 MPa, more preferably in the range of 650 to 1300 MPa.
[0068] The melting enthalpy of the pure heterophasic propylene copolymer may be in the range of 60 to 95 J / g, preferably in the range of 65 to 93 J / g, more preferably in the range of 68 to 90 J / g.
[0069] The simply supported beam NIS / 23°C of pure heterophasic propylene copolymers can be between 5.0 and 100.0 kJ / m 2 In the range of 15.0 to 90.0 kJ / m 2 In the range of 20.0 to 80.0 kJ / m 2 within the range.
[0070] The simply supported beam NIS / -20℃ of pure heterophasic propylene copolymers can be between 1.0 and 20 kJ / m 2 In the range of 2.0 to 15 kJ / m 2 In the range of 2.5 to 12.0 kJ / m 2 within the range.
[0071] Nucleating agent:
[0072] The heterophasic polypropylene composition of the present invention comprises 0.01 to 1.0 wt.-% (based on the total weight of the heterophasic polypropylene composition) of nucleating agent.
[0073] The nucleating agent is selected from the group of following nucleating agents consisting of:
[0074] (i) monocarboxylic acids and polycarboxylic acids,
[0075] (ii) a salt of a phosphoric acid diester, and
[0076] (iii) a polymer nucleating agent,
[0077] (iv) sorbitol derivatives, and
[0078] (v) Triamide derivatives.
[0079] Thus, the nucleating agent may be selected from the group comprising:
[0080] (i) salts of monocarboxylic acids and polycarboxylic acids, for example sodium benzoate or aluminum tert-butylbenzoate; or calcium salt of 1,2-cyclohexanedicarboxylate, of which calcium salt of 1,2-cyclohexanedicarboxylate is particularly preferred;
[0081] (ii) salts of phosphoric acid diesters, such as sodium 2,2'-methylenebis(4,6-di-tert-butylphenyl)phosphate or bis[2,2'-methylene-bis(4,6-di-tert-butylphenyl)phosphate]hydroxyaluminum and hydroxybis(2,4,8,10-tetra-tert-butyl-6-hydroxy12H-dibenzo(d,g)(1,3,2)dioxaphosphocin 6-oxidato)aluminium, also known as bis(2,4,8,10-tetra-tert-butyl-6-hydroxy-12H-dibenzo(d,g)(1,3,2)dioxaphosphooctane 6-oxido)hydroxyaluminium), of which bis(2,4,8,10-tetra-tert-butyl-6-hydroxy-12H-dibenzo(d,g)(1,3,2)dioxaphosphooctane 6-oxido)hydroxyaluminium or sodium 2,2'-methylenebis(4,6,-di-tert-butylphenyl)phosphate is preferred;
[0082] (iii) crystalline polymers such as poly(vinylcyclohexane) (PVCH), poly(4-methylpentene-1) (P4MP) and poly(tetrafluoroethylene), of which PVCH is preferred;
[0083] (iv) sorbitol derivatives, for example di(alkylbenzylidene)sorbitols, such as 1,3:2,4-dibenzylidene sorbitol, 1,3:2,4-di(4-methylbenzylidene)sorbitol, 1,3:2,4-di(4-ethylbenzylidene)sorbitol and 1,3:2,4-bis(3,4-dimethylbenzylidene)sorbitol, and nonitol derivatives, for example 1,2,3-trideoxy-4,6;5,7-bis-O-[(4-propylphenyl)methylene]nonitol; and
[0084] (v) Benzene-triamides, such as substituted 1,3,5-benzenetriamides, such as N,N',N"-tri-tert-butyl 1,3,5-benzenetricarboxamide, N,N',N"-tri-cyclohexyl-1,3,5-benzenetricarboxamide and N-[3,5-bis-(2,2-dimethyl-propionamido)-phenyl]-2,2-dimethyl-propionamide. It is especially preferred that the at least one α-nucleating agent (c) in the heterophasic polypropylene composition of the present invention is selected from 1,3:2,4-dibenzylidene sorbitol, 1,3:2,4-bis(3,4-dimethylbenzylidene)sorbitol, 1,2,3-trideoxy-4,6;5,7-bis-O-[(4-propylphenyl)methylene]nonitol and N-[3,5-bis-(2,2-dimethylpropionamido)-phenyl]-2,2-dimethyl-propionamide.
[0085] In a preferred embodiment the heterophasic polypropylene composition does not comprise a polymeric nucleating agent.
[0086] The following nucleating agents are referred to as polymeric nucleating agents and are therefore not contemplated in the preferred embodiments of the present invention:
[0087] Crystalline polymers such as poly(vinylcyclohexane) (PVCH), poly(4-methylpentene-1) (P4MP) and poly(tetrafluoroethylene), of which PVCH is preferred;
[0088] In certain embodiments, particularly preferred are those listed in group (i) or (ii), ie insoluble nucleating agents.
[0089] Particularly preferred are insoluble nucleating agents and non-polymeric nucleating agents listed in group (i) or (ii), and particularly preferred are bis(2,4,8,10-tetra-tert-butyl-6-hydroxy-12H-dibenzo(d,g)(1,3,2)dioxaphosphooctane 6-oxide)hydroxyaluminum or sodium 2,2'-methylenebis(4,6,-di-tert-butylphenyl)phosphate.
[0090] additive:
[0091] The heterophasic polypropylene composition according to the present invention may further comprise conventional additives in an amount up to 5.0 wt.-%, preferably in an amount of 0.1 to 2.0 wt.-%, more preferably in an amount of 0.3 to 1.0 wt.-%. Examples of additives include but are not limited to stabilizers such as antioxidants (e.g. hindered phenols, phosphites / phosphonates, sulfur-containing antioxidants, alkyl radical scavengers, aromatic amines, hindered amine stabilizers or blends thereof), metal deactivators (e.g. Irganox MD 1024) or UV stabilizers (e.g. hindered amine light stabilizers). Other typical additives are modifiers, such as antistatic agents or antifogging agents (e.g. ethoxylated amines and amides or glycerides), acid scavengers (e.g. calcium stearate) and blowing agents for foaming. Other modifiers are lubricants and resins (e.g. ionomer waxes, polyethylene copolymer waxes and ethylene copolymer waxes, Fischer-Tropsch waxes, montan wax-based waxes, fluorine-based compounds or paraffin waxes), as well as slip agents and anti-caking agents (e.g. erucamide, oleamide, talc, natural and synthetic silica or zeolites) and mixtures thereof.
[0092] It is also to be understood that the polymer introduced as carrier for a masterbatch or the like may be present in the heterophasic polypropylene composition in the range of 0.1 to 5.0 wt.-%, even in case the claims are formulated in closed wording ("heterophasic polypropylene composition consisting of ...").
[0093] Mechanical properties:
[0094] The heterophasic polypropylene composition of the present invention can be characterized by its physical properties, i.e. mechanical properties:
[0095] The flexural modulus according to ISO 178 may be in the range of 600 to 2500 MPa, preferably in the range of 700 to 2000 MPa, more preferably in the range of 850 to 1700 MPa.
[0096] Notched impact strength measured at +23°C according to ISO179, simple supported beam NIS / 23°C can be between 5.0 and 100.0 kJ / m 2 In the range of 15.0 to 90.0 kJ / m 2 In the range of 20.0 to 80.0 kJ / m 2 within the range.
[0097] In certain embodiments, the simply supported beam NIS / 23°C may be between 35 and 90 kJ / m 2 In the range of 60 to 85 kJ / m 2 .
[0098] Notched impact strength measured at -20°C according to ISO179, simple supported beam NIS / -20°C can be between 1.0 and 20 kJ / m 2 In the range of 2.0 to 15 kJ / m 2 In the range of 2.5 to 12.0 kJ / m 2 within the range.
[0099] Ideally, the heterophasic polypropylene composition may have a flexural modulus according to ISO 178 in the range of 600 to 2500 MPa, preferably in the range of 700 to 2000 MPa or 850 to 1700 MPa, and optionally has either or both of the following:
[0100] Charpy notched impact strength measured at +23°C according to ISO179 is between 5.0 and 100.0 kJ / m 2 In the range of 15.0 to 90.0 kJ / m 2 In the range of 20.0 to 80.0 kJ / m 2 within the scope of, and / or
[0101] Charpy notched impact strength measured at -20°C according to ISO179 is between 1.0 and 20 kJ / m 2 In the range of 2.0 to 15 kJ / m 2 range, or 2.5 to 12.0 kJ / m 2 within the range.
[0102] Aggregation methods
[0103] The heterophasic propylene copolymer comprised by the instant heterophasic polypropylene composition is preferably produced by sequential polymerization, wherein in one step a crystalline matrix being a propylene homo- or copolymer is produced and in a subsequent step an amorphous propylene-ethylene elastomer is produced in the presence of said propylene homo- or copolymer.
[0104] Therefore, amorphous propylene ethylene elastomer is not present as a separate fraction.
[0105] The process for polymerizing the heterophasic propylene copolymer comprised by the heterophasic polypropylene composition comprises polymerizing propylene in the presence of a single site catalyst in at least two, preferably two, polymerization steps, wherein
[0106] a) polymerizing propylene and optionally comonomers in a first polymerization reactor to obtain a crystalline matrix being a propylene homopolymer or copolymer, transferring said matrix to a second polymerization reactor, preferably a gas phase reactor (GPR),
[0107] b) In a second polymerization reactor, an amorphous propylene-ethylene elastomer is produced in the presence of the above-mentioned propylene homopolymer or copolymer.
[0108] Consecutively, the nucleating agent can be introduced into the heterophasic propylene copolymer by a compounding step or as a masterbatch to form the heterophasic polypropylene composition of this invention.
[0109] The process may be preceded by one or more prepolymerization steps.
[0110] catalyst
[0111] Catalyst system:
[0112] The heterophasic polypropylene composition according to this invention is preferably obtainable by a catalyst system comprising a single site catalyst, more preferably a metallocene catalyst complex and a cocatalyst.
[0113] Particularly preferred catalysts are:
[0114] Racemic-trans-dimethylsilylene[2-methyl-4,7-bis-(3',5'-dimethylphenyl)-1,5,6,7-tetrahydro-s-indacen-1-yl][2-methyl-4-(3',5'-di-tert-butyl-phenyl)-5-methoxy-6-tert-butylinden-1-yl]zirconium dichloride, or
[0115] rac-trans-dimethylsilylene[2-methyl-4-(3',5'-dimethylphenyl)-1,5,6,7-tetrahydro-s-indacene-1-yl][2-methyl-4-(3',5'-dimethylphenyl)-5-methoxy-6-tert-butylinden-1-yl]zirconium dichloride).
[0116] Catalyst
[0117] In order to form an active catalytic species, it is generally necessary to use a promoter known in the art.
[0118] According to the present invention, a cocatalyst system comprising a boron-containing cocatalyst and an aluminoxane cocatalyst is used in combination with the metallocene catalyst complex defined above.
[0119] The aluminoxane cocatalyst may be a catalyst having formula (I):
[0120]
[0121] wherein n is 6 to 20 and R has the following meanings.
[0122] Aluminoxanes are formed upon partial hydrolysis of organoaluminum compounds, such as those having the formula AlR3, AlR2Y, and Al2R3Y3, wherein R can be, for example, C1-C 10 Alkyl, preferably C1-C5 alkyl, or C 3-10 Cycloalkyl, C7-C 12 Aralkyl or alkaryl and / or phenyl or naphthyl, and wherein Y can be hydrogen, halogen, preferably chlorine or bromine, or C1-C 10 The alkoxy group is preferably a methoxy group or an ethoxy group. The oxygen-containing aluminoxane obtained is usually not a pure compound but a mixture of oligomers of the formula (II).
[0123] The preferred aluminoxane is methylaluminoxane (MAO).Since the aluminoxanes used as cocatalysts according to the invention are not pure compounds due to the way they are prepared, the molar concentrations of the aluminoxane solutions hereinafter are based on their aluminum content.
[0124] Additionally, boron-containing cocatalysts are used in combination with aluminoxane cocatalysts.
[0125] The catalyst complex desirably comprises a cocatalyst, preferably certain boron-containing cocatalysts. Thus, particularly preferred borates for use in the present invention comprise trityl ions, i.e., triphenylcarbonium ions. Thus, the use of Ph3CB(PhF5)4 and the like is therefore particularly favored.
[0126] The catalyst system of the invention is used in supported form. The particulate support material used is silicon dioxide or a mixed oxide such as silicon dioxide-alumina, in particular silicon dioxide.
[0127] Preferably a silica support is used. The skilled person is aware of the procedures required to support the metallocene catalyst.
[0128] In a preferred embodiment, the catalyst system corresponds to ICS3 of EP19177308.4.
[0129] Products
[0130] The present invention also covers final articles, especially shaped articles comprising the inventive heterophasic polypropylene composition.
[0131] The articles may be injection molded and may be used for packaging purposes or for applications in the automotive industry.
[0132] Preferably, the article has a wall thickness of 0.1 to 3.0 mm, such as 0.5 to 2.5 mm, for example 1.0 to 2.0 mm.
[0133] The present invention will now be described in more detail by way of the examples provided below:
[0134] Example
[0135] Measurement method
[0136] Melt flow rate
[0137] The melt flow rate (MFR2) is determined according to ISO 1133 and is expressed in g / 10 min. The MFR indicates the fluidity and, therefore, the processability of a polymer. The higher the melt flow rate, the lower the viscosity of the polymer. The MFR2 of polypropylene is determined at a temperature of 230°C and a load of 2.16 kg.
[0138] Differential Scanning Calorimetry (DSC)
[0139] Differential scanning calorimetry (DSC) analysis, melting temperature (T m ) and melting enthalpy (H m ), crystallization temperature (T c ) and heat of crystallization (H c , H CR ) 5 to 7 mg samples were measured using a TA Instrument Q200 differential scanning calorimeter (DSC). DSC was run according to ISO 11357 / Part 3 / Method C2 with a heating / cooling / heating cycle in the temperature range of -30 to +225°C at a scanning rate of 10°C / min. The crystallization temperature (T c ) and heat of crystallization (H c ) is determined by the cooling step, while the melting temperature (T m ) and melting enthalpy (H m ) is determined by the second heating step.
[0140] Xylene Cold Solubles (XCS)
[0141] The xylene cold soluble fraction at room temperature (XCS, wt. %) was determined according to ISO 16152; 5th edition; 2005-07-01 at 25°C.
[0142] Flexural modulus
[0143] Flexural modulus according to ISO 178 at 23°C for 80×10×4 mm injection molded according to EN ISO 1873-2 3 Measured by 3-point bending on the test bar.
[0144] The delta flex modulus defines the difference in flexural modulus between the nucleated polymer and the non-nucleated polymer.
[0145] Notched Impact Strength (NIS)
[0146] Notched impact strength (NIS) was measured according to ISO 179 1eA at +23°C or -20°C using a 80×10×4 mm2 test piece prepared according to EN ISO 1873-2. 3 Measured on injection molded bar specimens.
[0147] Crystex analysis
[0148] Crystalline fraction and soluble fraction method
[0149] The crystalline fraction (CF) and the soluble fraction (SF) of the polypropylene (PP) composition as well as the comonomer content and the intrinsic viscosity of each fraction and the comonomer content of the final polymer were analyzed by CRYSTEX QC, Polymer Char (Valencia, Spain).
[0150] Figure 1a shows a schematic diagram of the CRYSTEX QC instrument. As shown in Figure 1b, the crystalline fraction and the amorphous fraction are separated by a temperature cycle of dissolution at 160°C, crystallization at 40°C and redissolution in 1,2,4-trichlorobenzene (1,2,4-TCB) at 160°C. The quantification of SF and CF and the determination of the ethylene content (C2) are achieved by an infrared detector (IR4) and an online 2-capillary viscometer for the determination of the intrinsic viscosity (IV).
[0151] The IR4 detector is a multi-wavelength detector that detects IR absorbance at two different bands (CH3 and CH2) and is used to determine the concentration and ethylene content in ethylene-propylene copolymers. The IR4 detector is calibrated using a series of 8 EP copolymers with known ethylene contents ranging from 2 wt% to 69 wt% (determined by 13C-NMR), with various concentrations of each EP copolymer used for calibration ranging from 2 to 13 mg / ml.
[0152] By means of the XS calibration, the amounts of the soluble fraction (SF) and the crystalline fraction (CF) are related to the amount of "xylene cold solubles" (XCS) and the xylene cold insoluble (XCI) fraction, respectively, determined according to the standard gravimetric method per ISO 16152. The XS calibration was achieved by testing various EP copolymers with XS contents ranging from 2 to 31 wt%.
[0153] The intrinsic viscosity (IV) of the parent EP copolymer and its soluble and crystalline fractions was determined using an online 2-capillary viscometer and related to the corresponding IV determined by the standard method in decalin according to ISO 1628. Calibration was achieved with various EP, PP copolymers with IV = 2-4 dL / g.
[0154] The PP composition sample to be analyzed was weighed out at a concentration of 10 mg / ml to 20 mg / ml. After automatically filling the vial with 1,2,4-TCB containing 250 mg / l of 2,6-tert-butyl-4-methylphenol (BHT) as an antioxidant, the sample was dissolved at 160°C under continuous stirring at 800 rpm until completely dissolved, usually for 60 minutes.
[0155] As shown in Figures 1a and 1b, a defined volume of sample solution is injected into a column filled with an inert carrier, in which crystallization of the sample and separation of the soluble fraction from the crystalline part occur. This process is repeated twice. During the first injection, the entire sample is measured at high temperature, and IV [dl / g] and C2 [wt%] of the PP composition are determined. During the second injection, the soluble fraction (at low temperature) and the crystalline fraction (at high temperature) with a crystallization period are measured (SF wt%, C2 wt%, IV).
[0156] EP refers to ethylene propylene copolymer.
[0157] PP means polypropylene.
[0158] Quantification of microstructure by NMR spectroscopy
[0159] Quantitative nuclear magnetic resonance (NMR) spectroscopy was used to quantify the isotacticity and regioregularity of propylene homopolymers.
[0160] Adopt 1 H and 13 Quantitative NMR was recorded in solution on a Bruker Advance III 400 NMR spectrometer operating at 400.15 and 100.62 MHz, respectively. 13 C{1H}NMR spectra. All spectra were obtained using 13 The C-optimized 10 mm extended temperature probe was recorded at 125 °C, using nitrogen for all pneumatics.
[0161] For propylene homopolymers, about 200 mg of material was dissolved in 1,2-tetrachloroethane-d2 (TCE-d2). To ensure a homogeneous solution, the NMR tube was further heated in a rotary oven for at least 1 hour after the initial sample was prepared in a heating block. After insertion into the magnet, the tube was rotated at 10 Hz. This setting was chosen primarily for the high resolution required for quantification of the stereoregularity distribution (Busico, V., Cipullo, R., Prog. Polym. Sci. 26 (2001) 443; Busico, V.; Cipullo, R., Monaco, G., Vacatello, M., Segre, AL, Macromolecules 30 (1997) 6251). Standard single pulse excitation was used, using NOE and a two-stage WALTZ16 decoupling scheme (Zhou, Z., Kuemmerle, R., Qiu, X., Redwine, D., Cong, R., Taha, A., Baugh, D. Winniford, B., J. Mag. Reson. 187 (2007) 225; Busico, V., Carbonniere, P., Cipullo, R., Pellecchia, R., Severn, J., Talarico, G., Macromol. Rapid Commun. 2007, 28, 11289). A total of 8192 (8k) transient signals were obtained for each spectrum.
[0162] A proprietary computer program was used to quantify 13 C{ 1 H} NMR spectra are processed, integrated and relevant quantitative properties are determined from the integrals.
[0163] For propylene homopolymers, all chemical shifts are internally referenced to the methyl isotactic pentad (mmmm) at 21.85 ppm.
[0164] Characteristic signals corresponding to regio defects (Resconi, L., Cavallo, L., Fait, A., Piemontesi, F., Chem. Rev. 2000, 100, 1253; Wang, WJ., Zhu, S., Macromolecules 33 (2000), 1157; Cheng, HN, Macromolecules 17 (1984), 1950) or comonomers were observed.
[0165] The stereoregularity distribution is quantified by integration of the methyl region between 23.6-19.7 ppm, correcting for any sites not related to the stereo sequence of interest (Busico, V., Cipullo, R., Prog. Polym. Sci. 26 (2001) 443; Busico, V., Cipullo, R., Monaco, G., Vacatello, M., Segre, AL, Macromolecules 30 (1997) 6251).
[0166] Specifically, the effects of regio defects and comonomers on the quantification of the tacticity distribution were corrected by subtracting representative regio defect and comonomer integrals from the specific integrated region of the stereo sequence.
[0167] Isotacticity is determined at the pentad level and reported as the percentage of isotactic pentad (mmmm) sequences over all pentad sequences:
[0168] [mmmm]% = 100*(mmmm / sum of all quintuples)
[0169] The presence of 2,1-erythro regio defects is indicated by the presence of two methyl sites at 17.7 and 17.2 ppm and confirmed by other characteristic sites. No characteristic signals corresponding to other types of regio defects were observed (Resconi, L., Cavallo, L., Fait, A., Piemontesi, F., Chem. Rev. 2000, 100, 1253).
[0170] The amount of 2,1-erythro regiodefects was quantified using the average integral of the two characteristic methyl sites at 17.7 and 17.2 ppm:
[0171] P 21e =(I e6 +I e8 ) / 2
[0172] 1,2 The number of primary insertion propenes was quantified based on the methyl region and corrected for sites not associated with primary insertions that were contained within this region and for primary insertion sites that were not contained within this region.
[0173] P 12 =I CH3 +P 12e
[0174] The total amount of propene was quantified as the sum of the primary inserted propene and all other regio defects present.
[0175] P 总 =P 12 +P21e
[0176] The mole percentage of 2,1-erythro regio defects for all propylene was quantified.
[0177] [21e] mol% = 100*(P 21e / P 总 )
[0178] Material Description:
[0179] Catalyst Description:
[0180] MC1
[0181] The catalyst used for PP-CE1 was MC1, (rac-trans-dimethylsilylene[2-methyl-4-phenyl-5-methoxy-6-tert-butyl-indenyl)(2-methyl-4-(4-tert-butylphenyl)indenyl)zirconium dichloride) which had been synthesized as described in E2 of WO 2013 / 007650.
[0182]
[0183] Figure 1: Metallocene MC1 used in PP-CE1
[0184] The catalyst system is prepared using a metallocene MC1 and a cocatalyst system of MAO. The catalyst is supported on silica.
[0185] MC2
[0186] The catalyst used for PP1 and PP2 was MC2, rac-trans-dimethylsilanylidene[2-methyl-4,8-bis-(3',5'-dimethylphenyl)-1,5,6,7-tetrahydro-s-indacen-1-yl][2-methyl-4-(3',5'-di-tert-butyl-phenyl)-5-methoxy-6-tert-butylinden-1-yl]zirconium dichloride.
[0187] The catalyst was prepared as disclosed on pages 40 and 55 of WO2019 / 179959 for MC3.
[0188] The catalyst system is prepared using metallocene MC2 and a co-catalyst system of MAO and boron. The catalyst is supported on silica.
[0189]
[0190] Figure 2: Metallocene MC2 for PP1 and PP2
[0191] Preparation of MAO-silica support.
[0192] A glass reactor equipped with a mechanical stirrer anchor stirrer was charged with silica (10.0 g) of the grade DM-L-303 of AGC Si-Tech Company pre-calcined at 600° C. Then toluene (50 mL) was added. The mixture was stirred under N2, and a MAO solution (25 mL, 30 wt % in toluene) from Lanxess was added through a cannula while maintaining the temperature at about 35° C. After the addition was complete, the solid was allowed to settle, and the supernatant was removed and discarded. Fresh toluene (50 mL) was added, and the mixture was then heated to 80° C. and stirred at 80° C. for 1 hour. The slurry was allowed to settle and the mother liquor was filtered off. At 80° C., the catalyst was washed twice with toluene (50 mL), followed by settling and filtration. The reactor was cooled to 60° C. and the solid was washed with heptane (50 mL). Finally, the MAO-treated SiO2 was dried under vacuum at 60° C. for 2 hours. The MAO-treated support was collected as a free-flowing white powder (13 g).
[0193] Catalyst preparation
[0194] In a glove box filled with nitrogen, a solution of 0.25 mL of MAO (30% by weight in toluene, AXION 1330CALanxess) in dry toluene (1 mL) was added to aliquots of metallocene MC-D85 (39.0 mg, 39 μmol). The mixture was stirred at room temperature for 30 minutes. Next, tetrakis (perfluorophenyl) boric acid trityl ester (Boulder) (36.0 mg, 39 μmol) was added and the solution was stirred at room temperature for another 30 minutes. Next, 1.0 g of MAO-treated silica prepared as described above was placed in a glass vial. Then, a solution of metallocene, MAO and boric acid trityl ester in toluene was slowly added to the carrier and gently mixed over a 5-minute process. The resulting mixture was fully shaken and placed overnight. Anhydrous toluene (5 mL) was then added, and the slurry was fully mixed with inert gas bubbling for more than 10 minutes. Solids were allowed to settle, and the liquid was filtered off and discarded. The resulting filter cake was dried in vacuo for 1 hour to yield 1.0 g of the catalyst as a pink free-flowing powder.
[0195] MC3
[0196] The catalyst used for PP3 was MC3, rac-trans-dimethylsilanylidene[2-methyl-4-(3',5'-dimethylphenyl)-1,5,6,7-tetrahydro-s-indacen-1-yl][2-methyl-4-(3',5'-dimethylphenyl)-5-methoxy-6-tert-butylinden-1-yl]zirconium dichloride synthesized according to the procedure described in WO2019 / 007655, pp 49ff.
[0197]
[0198] Figure 3: Metallocene MC3 for PP3
[0199] Preparation of MAO-silica carrier
[0200] A steel reactor equipped with a mechanical stirrer and a filter screen was flushed with nitrogen and the reactor temperature was set to 20°C. Then, silica (5.0 kg) of the grade DM-L-303 of AGC Si-Tech Company, pre-calcined at 600°C, was added from the feed bucket, followed by careful nitrogen pressurization and decompression using a manual valve. Toluene (22 kg) was then added. The mixture was stirred for 15 min. Then, a 30 wt % solution (9.0 kg) of MAO from Lanxess in toluene was added through the feed line at the top of the reactor within 70 min. The reaction mixture was then heated to 90°C and stirred at 90°C for another 2 hours. The slurry was allowed to settle and the mother liquor was filtered off. At 90°C, the catalyst was washed twice with toluene (22 kg), followed by settling and filtering. The reactor was cooled to 60°C and the solid was washed with heptane (22.2 kg). Finally, the MAO treated SiO2 was dried at 60° under a nitrogen stream for 2 hours and then dried under vacuum (-0.5 bar, gauge) with stirring for 5 hours. The MAO treated support was collected as a free flowing white powder which was found to contain 12.2 wt% Al.
[0201] Catalyst preparation
[0202] At 20°C, 30 wt% MAO in toluene (0.7 kg) was added to a steel reactor under nitrogen protection via a burette. Toluene (5.4 kg) was then added under stirring. MC3 (93 g) as described above was added from a metal cylinder, followed by rinsing with 1 kg of toluene. The mixture was stirred for 60 minutes at 20°C. Trityl tetrakis(pentafluorophenyl)borate (91 g) was then added from a metal cylinder, followed by rinsing with 1 kg of toluene. The mixture was stirred for 1 h at room temperature. The resulting solution was added to the stirred cake of the MAO-silica support prepared as above over a period of more than 1 hour. The cake was left for 12 hours, then dried for 2 hours at 60°C under a stream of N2, and dried for another 5 hours under vacuum (-0.5 bar, gauge pressure) under stirring. The dried catalyst was sampled in the form of a pink free-flowing powder containing 13.9% Al and 0.11% Zr.
[0203] The polymerization was carried out in a 25 L laboratory scale reactor. The details of the polymerization are shown in Table 1.
[0204] Table 1: Aggregate data
[0205] PP-CE1 PP1 PP2 PP3 catalyst MC1 MC2 MC2 MC3 Prepolymerization Dwell time min 10 10 10 10 H2 nl 0 0 0 0 Main step = ring pipe temperature ℃ 75 75 75 75 Total H2 nl 2 2 2 2 Dwell time min 30 30 30 30 Split Ratio weight% 43 82 80 78 First gas phase polymerization temperature ℃ 80 70 70 70 Total H2 nl 2.0 0 0.1 0 Dwell time min 90 90 90 90 C2 / C3 wt% / wt% 0.05 0.83 0.82 0.69 pressure bar, gauge 21 25 25 16 Split Ratio weight% 41 18 20 22 Second gas phase polymerization temperature ℃ 75 Not used Not used Not used Total H2 nl 0 Dwell time min 90 C2 / C3 wt% / wt% 0.67 pressure bar, gauge 16 Split Ratio weight% 16
[0206] All base polymers were produced in laboratory scale reactors.
[0207] The polymer powder was stabilized with 1500 ppm of Irganox B225 (supplied by BASF) and 500 ppm of synthetic hydrotalcite (MAHC).
[0208] The core polymer contained 2000 ppm of NA 21 commercially available from Adeka.
[0209] CE2 is disclosed as CE1 in WO2020 / 011825.
[0210] PP-CE3 corresponds to the sample ID “M-iPP (cycled)” disclosed in Table 1 on page 486 of M. Varma-Nair et al.: “Quiescent crystallization kinetics of nucleated metallocene and ZN isotactic polypropylenes” (Journal of Thermal Analysis and Calorimetry, 59 (2000) pp. 483-495).
[0211] CE3 corresponds to the sample ID “M-iPP+0.2% α-nucleating agent” disclosed in Table 1 on page 486 of M. Varma-Nair et al.: “Quiescent crystallization kinetics of nucleated metallocene and ZN isotactic polypropylenes” (Journal of Thermal Analysis and Calorimetry, 59 (2000) pp. 483-495).
[0212] Table 2: Polymer properties of heterophasic propylene copolymers used in the inventive examples and comparative examples
[0213] CE1 CE2 CE3 IE1 IE2 IE3 polymer: PP-CE1 PP-CE3 PP1 PP2 PP3 <![CDATA[MFR 230 / 2.16 ]]> g / 10min 4.0 2.5 2.8 5.0 6.0 1.0 Crystex: Soluble fraction (SF) weight% 18 12 <1.0 17 19 23 C2(Total) weight% 5.9 2.3 0 6 . 6.8 C2(SF) weight% 19 17.1 0 27 28.2 23.9 C2(CF) weight% 3.4 1.3 0 2.6 2.5 1.8 IV(SF) dl / g 1.8 1.9 Undetermined 3.6 3.6 2.5 IV(CF) dl / g 2.2 2.3 Undetermined 2.0 1.9 2.9 IV(SF) / IV(CF) ratio - 0.82 0.83 - 1.80 1.89 0.86 NMR: <mmmm>Matrix < / mmmm> % Undetermined 99.4 Undetermined 99.7 99.7 99.4 <2,1>Regional Defects Mole % Undetermined 0.7 Undetermined 0.9 0.9 0.7
[0214] Table 3: Mechanical properties of heterophasic propylene copolymers (unnucleated)
[0215] PP-CE1 PP-CE3 PP1 PP2 PP3 Used in the examples: CE1 CE3 IE1 IE2 IE3 Flexural modulus MPa 493 1056 998 786 Tc ℃ 108 114.8 118 118 115 Tm1 ℃ 145 154.8 160 160 157 Hm1 J / g 63 86 84 77 NIS / 23℃ <![CDATA[kJ / m 2 ]]> 61 25.1 45.2 77.2 NIS / -20℃ <![CDATA[kJ / m 2 ]]> 1.3 5.7 6.4 2.9
[0216] Table 4: Mechanical properties of heterophasic propylene compositions of comparative examples and inventive examples
[0217]
[0218] Table 4 clearly shows that the inventive examples IE1, IE2 and IE3 have a specific combination of polymer characteristics and meet the requirements in terms of crystallization temperature. The object of the present invention is achieved.
Claims
1. A heterophasic polypropylene composition comprising a) 99.0 to 99.99 wt.% of a heterophasic propylene copolymer, and b) 0.01 to 1.0% by weight of a nucleating agent selected from the group consisting of salts of monocarboxylic acids, polycarboxylic acids and phosphoric acid diesters, wherein the heterophasic propylene copolymer is characterized by comprising i) 69.0 to 88.0 wt.% of a crystalline matrix which is a propylene homopolymer or copolymer, The crystalline matrix corresponds to the crystalline fraction determined according to the CRYSTEX QC method, ISO 6427-B, having an intrinsic viscosity in the range of 1.3 to 3.7 dl / g, and contains 1.5 to 3.5% by weight of comonomer, and ii) 12.0 to 31.0 wt.% of an amorphous propylene-ethylene elastomer dispersed in the crystalline matrix, optionally containing as a further comonomer a C4-C12 alpha-olefin, said amorphous propylene-ethylene elastomer corresponding to the soluble fraction determined according to the CRYSTEXQC method, ISO 6427-B, and having an intrinsic viscosity in the range of 2.2 to 4.5 dl / g, and Containing 21.5 to 33.0% by weight of comonomer, wherein the crystalline matrix and the amorphous propylene-ethylene elastomer total 100 wt%, and wherein the ratio of the intrinsic viscosity of the soluble fraction to the intrinsic viscosity of the crystalline fraction is in the range of 0.85 to 2.2, Features The heterophasic polypropylene composition has a crystallization temperature of at least 124 °C, 2,1-erythro regio defects in an amount of 0.3 to 2.0 wt.-% and an intrinsic viscosity of the soluble fraction in the range of 2.0 to 5.0 dl / g.
2. The heterophasic polypropylene composition according to claim 1, comprising i) 72.0 to 86.0 wt.-% of a crystalline matrix which is a propylene homopolymer or copolymer, which corresponds to the crystalline fraction determined according to the CRYSTEX QC method, ISO 6427-B and contains 1.5 to 3.5 wt.-% of comonomer, and ii) 14.0 to 28.0 wt.-% of amorphous propylene-ethylene elastomer dispersed in said crystalline matrix, optionally comprising one or more C4-C12 α-olefins as further comonomers, said amorphous propylene-ethylene elastomer corresponding to said soluble fraction determined according to the CRYSTEX QC method, ISO 6427-B.
3. The heterophasic polypropylene composition according to claim 1 or 2, having a melting temperature Tm of at least 155 °C.
4. The heterophasic polypropylene composition according to claim 1 or 2, having an MFR according to ISO 1133 in the range of 0.1 to 100 g / 10 min. 230 / 2.16 .
5. The heterophasic polypropylene composition according to claim 1 or 2, wherein the heterophasic propylene copolymer has a total comonomer content in the range of 1.0 to 10.0 wt.-%.
6. The heterophasic polypropylene composition according to claim 1 or 2, wherein the heterophasic propylene copolymer has a comonomer content in the soluble fraction in the range of 22.5 to 31.0 wt.-%.
7. The heterophasic polypropylene composition according to claim 1 or 2, wherein the heterophasic propylene copolymer has an intrinsic viscosity of the soluble fraction in the range of 2.3 to 4.0 dl / g, and / or The intrinsic viscosity of the crystalline fraction is in the range of 1.5 to 3.4 dl / g.
8. The heterophasic polypropylene composition according to claim 1 or 2, having 2,1-erythro regio defects in an amount in the range of 0.5 to 1.5 wt.-%.
9. The heterophasic polypropylene composition according to claim 1 or 2, having 2,1-erythro regio defects in an amount in the range of 0.6 to 1.2 wt.-%.
10. The heterophasic polypropylene composition according to claim 1 or 2, having a crystallization temperature in the range of at least 124 to 135 °C.
11. The heterophasic polypropylene composition according to claim 1 or 2, wherein the nucleating agent is selected from bis(2,4,8,10-tetra-tert-butyl-6-hydroxy-12H-dibenzo(d,g)(1,3,2)dioxaphosphooctane 6-oxide)hydroxyaluminum or sodium 2,2'-methylenebis(4,6,-di-tert-butylphenyl)phosphate.
12. The heterophasic polypropylene composition according to claim 1 or 2, wherein the heterophasic polypropylene composition has a flexural modulus according to ISO 178 in the range of 600 to 2500 MPa, and optionally has either or both of the following: 5.0 to 100.0 kJ / m 2 Charpy notched impact strength measured at +23°C according to ISO 179 within the range of 1.0 to 20 kJ / m 2 The Charpy notched impact strength is measured at -20°C according to ISO 179 within the range of .
13. A shaped article comprising the heterophasic polypropylene composition according to any one of claims 1 to 12.
14. Use of the heterophasic polypropylene composition according to any of claims 1 to 12 for the production of shaped articles.
Citation Information
Patent Citations
Heterophasic polypropylene with high flowability and excellent low temperature impact properties
EP2075284A1
catalysts
WO2013007650A1
Process for preparing heterophasic propylene copolymers
WO2019007655A1
Single-site catalyst based impacted copolymers with excellent mechanical and optical properties
WO2019134951A1
Heterophasic polypropylene composition with improved balance of properties
WO2020011825A1